Effect of an alcohol-free beer enriched with isomaltulose and a resistant dextrin on insulin resistance in diabetic patients with overweight or obesity. Issue 2 (February 2020) - Mateo-Gallego, Rocío; Pérez-Calahorra, Sofía; Lamiquiz-Moneo, Itziar; Marco-Benedí, Victoria; Bea, Ana M.; Fumanal, Antonio J.; Prieto-Martín, Ascensión; Laclaustra, Martín; Cenarro, Ana; Civeira, Fernando
Summary: Background & aims: The quality of carbohydrates has an essential role in nutritional management of type 2 diabetes mellitus (T2DM) because of its substantial impact on glucose homeostasis. Alcohol-free beer has beneficial bioactive components but it has a relatively high glycemic-index so its consumption is restricted in diabetic subjects. We aimed to explore the effect of an alcohol-free beer with modified carbohydrate composition almost completely eliminating maltose and adding isomaltulose (16.5 g/day) and a resistant maltodextrin (5.28 g/day) in comparison to a regular alcohol-free beer on glycemic control of diabetic subjects with overweight or obesity. Design: We randomized 41 subjects into two groups: a) consumption of 66 cL/day of; regular alcohol-free beer for the first 10 weeks and 66 cL/day of alcohol-free beer with modified carbohydrate composition for the next 10 weeks; b) the same described intervention in opposite order. There was a washout period for 6–8 weeks between the two interventions. Participants were counseled to adhere to a healthy diet for cardiovascular health and to increase physical activity. Clinical, biochemical, anthropometric, lifestyle and satiety assessments were performed at the beginning and at the end of each period. Results: Subjects showed significantly weight loss after the two ten weeks periods (−1.69 ± 3.21% and −1.77 ± 3.70% after experimental and regular alcohol-free beers, respectively, P = 0.881). Glucose and glycated hemoglobin did not significantly change after any period. Insulin concentrations and HOMA-IR significantly decreased (−11.1 [–21.3−4.64]% and −1.92 ± 32.8% respectively) after the intake of experimental alcohol-free beer but not after regular alcohol-free beer. Reductions remained statistically significant after adjusting for weight loss, energy intake, physical activity and intervention order. Subjects reported higher satiety scores after consuming experimental alcohol-free beer. Conclusions: An alcohol-free beer including the substitution of regular carbohydrates for low doses of isomaltulose and the addition of a resistant maltodextrin within meals led to an improvement in insulin resistance in subjects with T2DM and overweight or obesity. Clinical trial registration: The clinical trial has been registered in ClinicalTrials.gov (Identifier: NCT03337828 ).